Acute Poison-Related Mortality among Adults at a Tertiary Care Hospital Multan, Pakistan – A Cross Sectional Study (Medical Forum Monthly, 2021)
Objective: The objective of the study was to determine the acute poison-related mortality among adults at Nishtar Hospital, Multan.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the department of Medicine (unit-I) at Nishtar Hospital, Multan from January 01, 2019 to June 30, 2019.Materials and Methods: The patients were visited on daily basis to record any death of the patient with the history of poisoning and relative signs and symptoms during hospital stay. The SPSS-21 was used for statistical analysis. Mean and standard deviation were calculated for age, duration of poisoning and hospital stay. Frequency and percentages were calculated for gender, marital status, residence, ethnicity, employment, education, type of poisoning and mortality. Effect modifiers like age, gender, duration of poisoning and type of poisoning were controlled through stratification.Results: Of these 200 study cases, 66 (33%) were male patients while 134 (67%) were female patients. The mean age of the study cases was 23.4 ± 4.14 years. Of 200 patients, 111 (55.5%) patients were married, 87 (43.5%) were unmarried and 2 (1%) were divorced. Similarly, 70.5%, 22% and 6% patients belonged to Saraiki, Punjabi and Urdu ethnicity, respectively. The residence of 87.5% and 12.5% patients was rural and urban areas, respectively. Of 200 patients, 78% were unemployed while 22% were employed, respectively. Top three type of poisoning were paraphenylenediamine poisoning (51%), organophosphate (14%) and aluminium phosphide (10%). Suicidal, accidental and homicidal cases were 86.5%, 7.5% and 6%, respectively. Thirty-three (16.5%) patients died. Mean duration of poisoning at time of presentation and hospital stay were 7.37 ± 12.66 hours and 3.98 ± 4.06 days, respectively. Significant association between hospital stay and mortality was found (p = 0.002).Conclusion: Poison related mortality is significantly associated with hospital stay. Most of the deaths occurred within first three days of admission.